2020
DOI: 10.5223/pghn.2020.23.2.146
|View full text |Cite
|
Sign up to set email alerts
|

Liver Involvement in Children with Alpha-1 Antitrypsin Deficiency: A Multicenter Study

Abstract: Alpha-1 antitrypsin deficiency (A1ATD) in one of the most common genetic causes of liver disease in children. We aimed to analyze the clinical characteristics and outcomes of patients with A1ATD. Methods: This study included patients with A1ATD from five pediatric hepatology units. Demographics, clinical findings, genetics, and outcome of the patients were recorded (n=25). Results: Eight patients (32.0%) had homozygous PiZZ genotype while 17 (68.0%) had heterozygous genotype. Patients with PiZZ genotype had lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
1
6
0
1
Order By: Relevance
“…Compared with the Danish pediatric reference range of S-AAT (1.0-1.7 g/L) (11), the homozygotes were severely deficient of S-AAT while the heterozygotes were moderately deficient. Similarly, French and Turkish studies have reported mean and median S-AAT concentrations of 0.4 g/L ± 0.1 SD (31), 0.37 g/L ± 0.77 SD (25), and 0.35g/L (IQR: 0.23-0.77) (36) in homozygotes and 0.6 g/L ± 0.1 SD in heterozygotes (31). This suggests that an S-AAT value <0.5 g/L is a good indicator of ZZ-homozygosity, and it underlines the importance of genetic testing of children with S-AAT concentrations <1 g/L.…”
Section: Serum α 1 -Antitrypsinmentioning
confidence: 88%
“…Compared with the Danish pediatric reference range of S-AAT (1.0-1.7 g/L) (11), the homozygotes were severely deficient of S-AAT while the heterozygotes were moderately deficient. Similarly, French and Turkish studies have reported mean and median S-AAT concentrations of 0.4 g/L ± 0.1 SD (31), 0.37 g/L ± 0.77 SD (25), and 0.35g/L (IQR: 0.23-0.77) (36) in homozygotes and 0.6 g/L ± 0.1 SD in heterozygotes (31). This suggests that an S-AAT value <0.5 g/L is a good indicator of ZZ-homozygosity, and it underlines the importance of genetic testing of children with S-AAT concentrations <1 g/L.…”
Section: Serum α 1 -Antitrypsinmentioning
confidence: 88%
“…In children the heterozygous Pi*MZ genotype does not seem to be sufficient to develop a significant liver disease on its own (Figure 2). Transient neonatal cholestasis, mildly elevated liver tests and hepatomegaly may be seen in children, hence phenotyping and/or genotyping should be considered when the AAT level is below 1.1 g/L [20] [38]. On the other hand, carriage of one Pi*Z allele can probably act as a modifier of a simultaneously present pediatric chronic liver diseases.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Transient neonatal cholestasis, mildly elevated liver tests, and hepatomegaly may be seen in children; hence, phenotyping and/or genotyping should be considered when the AAT level is below 1.1 g/L. 20 38 On the other hand, carriage of one Pi*Z allele can probably act as a modifier of a simultaneously present pediatric chronic liver diseases. For example, patients with biliary atresia and a non-MM genotype were shown to need a liver transplantation earlier.…”
Section: Liver Disease In Childrenmentioning
confidence: 99%
“…Dentro del seguimiento, debe buscarse en forma dirigida el hepatocarcinoma, aunque su frecuencia es baja en la edad pediátrica. 18,19 Colestasis intrahepática familiar progresiva La identificación del gen involucrado (ATP8B1, ABCB11, ABCB4, TJP2, NR1H4, MYO5B) ha permitido realizar un tratamiento y seguimiento individual de estos pacientes. Los pacientes con CIFP1 (ATP8B1) y CIFP2 (ABCB11) pueden presentar colestasis, prurito y retraso pondoestatural con distintos grados de severidad desde las primeras semanas de vida.…”
Section: Las Complicaciones Más Frecuentes Sonunclassified